2021
DOI: 10.1515/jpem-2021-0587
|View full text |Cite
|
Sign up to set email alerts
|

A single-centre study of genetic mutations, audiology, echocardiogram and pulmonary function in Saudi children with osteogenesis imperfecta

Abstract: Objectives Osteogenesis imperfecta (OI) is a heterogeneous group of inherited connective tissue disorders, characterised by skeletal fragility. Patients with OI may also exhibit extra-skeletal features like blue or grey scleral colour, fragile skin, easy bruising, joint laxity, short stature, deafness, cardiac valve abnormalities and abnormal pulmonary function. The objective of this study is to describe genetic mutations, prevalence of hearing issues, cardiac complications and impaired pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In total 22 articles were included. Twelve case–control studies [ 12 , 22 26 , 29 34 ] and ten large case series ( n > 10)/cohort studies [ 10 , 35 43 ] were identified. A quality assessment (NHLBI) of the included articles was performed and showed that 10% of the studies were classified as poor, 37% as fair and 53% as good.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total 22 articles were included. Twelve case–control studies [ 12 , 22 26 , 29 34 ] and ten large case series ( n > 10)/cohort studies [ 10 , 35 43 ] were identified. A quality assessment (NHLBI) of the included articles was performed and showed that 10% of the studies were classified as poor, 37% as fair and 53% as good.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence varied between 0 in children (Ahmad et al . ) and 31.6% in both children and adults (White et al) [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%